2019
DOI: 10.1109/access.2019.2891282
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Availability Evaluation for Cloud Data Center Networks Using Hierarchical Models

Abstract: Modeling a cloud computing center is crucial to evaluate and predict its inner connectivity reliability and availability. Many previous studies on system availability/reliability assessment of virtualized systems consisting of singular servers in cloud data centers have been reported. In this paper, we propose a hierarchical modeling framework for the reliability and availability evaluation of tree-based data center networks. The hierarchical model consists of three layers, including 1) reliability graphs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 89 publications
0
16
0
1
Order By: Relevance
“…The proposed hierarchical models of the IoT smart factory infrastructure are all implemented in symbolic hierarchical automated reliability and performance evaluator (SHARPE) [58,59]. The input parameters are mostly based on previous experimental studies and consolidated works [19,27,[60][61][62] as shown (i) in Table 1 for default input parameters used in software/hardware sub-models of cloud member system, (ii) in Table 2 for default input parameters of software/hardware sub-models of fog member system, and (iii) in Table 3 for default input parameters of edge member system's software/hardware sub-models. The developed hierarchical model of the IoT smart factory infrastructure is analyzed in regard to various analysis outputs including (i) SSA, (ii) sensitivity of SSA wrt.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed hierarchical models of the IoT smart factory infrastructure are all implemented in symbolic hierarchical automated reliability and performance evaluator (SHARPE) [58,59]. The input parameters are mostly based on previous experimental studies and consolidated works [19,27,[60][61][62] as shown (i) in Table 1 for default input parameters used in software/hardware sub-models of cloud member system, (ii) in Table 2 for default input parameters of software/hardware sub-models of fog member system, and (iii) in Table 3 for default input parameters of edge member system's software/hardware sub-models. The developed hierarchical model of the IoT smart factory infrastructure is analyzed in regard to various analysis outputs including (i) SSA, (ii) sensitivity of SSA wrt.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Hierarchical models in practice are often developed in modeling and analysis of sophisticated and large-sized systems and/or multi-fold system of systems in order to reduce largeness of monolithic models and to prevent model computation and analysis processes from state-space explosion problems [18,19]. A hierarchical system model often consists of multi-level models in which (i) the upper levels are composed of non-state-space model types including FT or RBD, especially, for structured modeling of systems/subsystems, or reliability graph (RG) for network modeling [20], and (ii) the lower levels consists of state-space models (e.g., CTMC or SPN, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al [28], [29] provide a comprehensive dependability modeling of virtualized data centers. Their work covers the reliability and availability of different scenarios and virtualized architectures.…”
Section: Related Workmentioning
confidence: 99%
“…For a small range of N(Y), Cases 2 and 3 show improving result better than Case 1, whereas for large M(Y), Case 1 shows better results. e possible explanation for this is that (i) the processor availability reduces when both failure and repair rates increase, (ii) optimal value of M is larger for Case 1 than for Cases 2 and 3. e proposed reliability modelling using SPM is compared with other standard reliability models such as reliability graph model [36] and hierarchical correlation model (HCM) [11]. ese two models evaluate reliability in the cloud-based system.…”
Section: Numerical Analysismentioning
confidence: 99%